SAT0575 Disease Activity in Psoriatic Arthritis (PSA): Defining Remission and Treatment Success Using the Dapsa-Score. (9th June 2015) - Schoels, M.; Aletaha, D.; Alasti, F.; Haslacher, H.; Smolen, J.
Abstract : Background: The Disease Activity Index for Psoriatic Arthritis (DAPSA) is a valid, responsive and discriminative tool. Definitions of disease activity states and therapeutic response are still missing. Objectives: To derive such criteria for the DAPSA instrument. Methods: We retrieved 30 patient profiles from an observational database including joint counts, patient pain and global activity ratings, and C-reactive protein levels and carried out a survey among experts to classify patients into remission (REM); low (LDA), moderate (MDA), or high (HDA) disease activity. Based on each state's 25th and 75th percentiles of DAPSA values, we defined upper and lower thresholds. To define minor, moderate and major treatment response, we used Cohen's Kappa statistics and analysed agreement of DAPSA percent change with ACR20/50/70-response in three randomized controlled trials. Results: Our survey yielded a response rate of 75%. Mean DAPSA differed significantly between patients classified as REM, LDA, MDA, or HDA (p<0.001). Based on the respective DAPSA quartiles, we propose cut-off values of ≤4 for REM, >4 and ≤14 for LDA, >14 and ≤28 for MDA, and >28 for HDA. We observed best agreement of DAPSA with ACR20/50/70 response at DAPSA changes of 50/75/85% for minor, moderate and major improvement, respectively (Figure ). Cross-validation strongly supported these results. Conclusions: The DAPSA constitutes a disease-specific, validated, and feasible tool for PsA assessment. In this study, we provide criteria for disease activity states and for treatment response. They are based on an international expert survey, and are supported by good performance in clinical trials and observational data alike. Disclosure of Interest: None declared